Iron deficiency anemia as a multisystem disorder: linking molecular dysregulation to clinical outcomes - Sanjeyan N.; Nirmala K.; Indhumathi M. (International Journal of Basic & Clinical Pharmacology, 2026)
Iron deficiency anemia (IDA) is the most prevalent nutritional deficiency worldwide and remains a major public health challenge affecting children, women of reproductive age, pregnant women, and individuals with chronic diseases. Although traditionally regarded as a hematological disorder characterized by impaired hemoglobin synthesis and reduced oxygen-carrying capacity, increasing evidence indicates that iron deficiency produces multisystem dysfunction through disturbances in cellular metabolism, mitochondrial function, neurotransmitter synthesis, immune regulation, and iron homeostasis. This review summarizes the epidemiology, etiology, molecular pathophysiology, clinical manifestations, diagnostic evaluation, treatment strategies, and complications of IDA. Central to its pathogenesis is dysregulation of the hepcidin–ferroportin axis, leading to impaired iron absorption, defective erythropoiesis, and altered tissue iron utilization. Beyond anemia, iron deficiency contributes to cognitive impairment, reduced physical performance, cardiovascular stress, immune dysfunction, adverse pregnancy outcomes, and diminished quality of life. Early diagnosis using appropriate hematological and biochemical markers, together with timely identification of the underlying cause and individualized iron replacement therapy, is essential to prevent irreversible complications. A comprehensive understanding of the molecular mechanisms linking iron deficiency to systemic clinical manifestations may facilitate earlier diagnosis, optimize therapeutic strategies, and improve long-term patient outcomes.